The effect of hyperbaric oxygen 2.4 absolute atmospheres on transforming growth factor-β and matrix metalloproteinase-8 expression during orthodontic tooth movement in vivo. - Arya Brahmanta; Noengki Prameswari; Budi Handayani; Meralda Rossy Syahdinda (GarVal Editorial Ltda., 2021)
Context: Orthodontic force causes the compression of the periodontal ligament in inhibiting vascularization on the pressure side of orthodontic tooth movement (OTM), while on the opposite side, the periodontal ligament is stretched. Hyperbaric oxygen therapy (HBOT) can increase the dissolved oxygen in the blood, which can affect the tissue regeneration of the periodontal ligament. Aims: To evaluate the effect of HBO 2.4 absolute atmospheres (ATA) for 3 × 30 minutes with 5 minutes interval for 7 days as an adjuvant therapy to accelerate periodontal ligament remodeling during OTM in Cavia cobaya. Methods: The study was an experimental laboratory research with a completely randomized design. Twenty-four males C. cobaya were divided into three groups, (X1) as the control group, (X2) as the group with orthodontic force, and (X3) as the group with orthodontic force followed by HBO 2.4 ATA. Matrix Metalloproteinase (MMP)-8 and Transforming Growth Factor (TGF)-β expressions were measured by using immunohistochemistry. OTM was then examined by applying linear distance and analyzed by employing ratio test (p<0.05). Results: Ratio analysis shows HBO 2.4 ATA for 3 × 30 minutes once a day with 5 minutes intervals for 7 days has increased MMP-8 expressions in the pressure area and TGF-β in the tension area (p<0.05). Conclusions: HBO 2.4 ATA for 3 × 30 minutes once a day for 7 with 5 minutes intervals is able to effectively accelerate the periodontal ligament remodeling process expressed by the increased expression MMP-8, especially within the pressure area and TGF-β in the tension area.